Effects of tourism development on surface area of main lakes of Shchuchinsk-Burabay resort area, Kazakhstan - Ramazanova, Makhabbat (2019)
Lake (or lacustrine) water is one of the most sensitive and vulnerable resources for many tourist destinations, whose attractiveness highly depends on the water quality and availability in the lakes. The Shchuchinsk-Burabay resort area, located in the Akmola region of the Northern Kazakhstan, is one of the most popular tourist destinations of the country, known for its attractive natural landscape and for its great number of lakes. However, during the last decades, these lakes have been facing environmental issues due to their overexploitation and increasing level of pollution. Thus, the aim of the current study is to examine the changes in surface area of these lakes during the last 30 years by using GIS technologies, and the influence of tourism industry upon this phenomenon. Accommodation facilities (hotels, sanatoriums and guesthouses), as main tourism-related water consumers, have been targeted within our analysis. Results show that tourism is one of the factors responsible for surface area decline of the main lakes in the region, and its responsibility increases when combined with other factors. This study also formulates recommendations for water management policymakers in order to guarantee the sustainability of lake water as a key resource of the tourism industry in the region.